General Geographical Economics Model with Congestion - Charles van Marrewijk (Tinbergen Institute, 2005)
We derive and discuss a general, but simple geographical economics model with congestion, allowing us to explain the economic viability of small and large locations. The model generalizes some previous work and lends itself to analyzing the impact of public policy in terms of infrastructure changes. We show analytically that scale effects (total size of the economy) and changes in the cost structure (fixed and marginal costs) are important from a welfare perspective, but largely irrelevant from an economic dynamics perspective.
Keywords: F; O; R; 330; Geographical economics; congestion; externalities